PREVALENCE OF VIRUS DISEASES OF RIDGE GOURD (Luffa acutangula (L.) Roxb.) AND CHARACTERIZATION OF A MAJOR ASSOCIATED VIRUS - SANA T.; Dr. Radhika N. S. (Advisor ) (College of Agriculture Department of Plant Pathology, 2024)
The research work entitled "Prevalence of virus diseases of ridge gourd (Luffa acutangula (L.) Roxb.) and characterization of a major associated virus" was carried out in the Department of Plant Pathology, College of Agriculture, Padannakkad during 2021-23 with the objectives of assessment of virus diseases of ridge gourd in North Kerala; transmission studies, identification of sources of resistance, molecular detection and characterization of coat protein of major virus associated with the disease. Survey for assessment of virus disease incidence (DI) and vulnerability index (VI) of ridge gourd was conducted in major vegetable growing areas of Kozhikode, Kannur, and Kasaragod (AEU 2 and 11) districts during 2021-2023. It was found that the DI ranged from5.3-100 percent and VI from26.57-84.08. Kunjathur, Thalangady, and Hosabettu areas of Kasaragod district recorded the highest incidence (100%). The highest VI(84.08) was recorded in Thalangady (Kasaragod). Kuttyeri recorded high disease incidence (90%) and VI (61.2)in Kannur district. In Kozhikode district,Cherukulathur recorded high disease incidence (68%) and Poolacode recorded high VI (35.71). Plants in cultivated fields at Avala, Akkuparamb, and Velom were asymptomatic. Whiteflies and aphids associated with infected ridge gourd were identified as Bemisia tabaci and Aphis gossypii. Weeds like Synedrella sp., Ageratum conizoides and Alternanthera sp. were observed with chlorosis and vein banding symptoms in the surveyed areas. Light chlorotic specks with yellowing, pale green intermingled with normal green tissues, vein banding, yellow vein mosaic, cupping, blistering, vein clearing, thickening, reduction in leaf size, puckering, and green island symptoms were observed. The infected scions collected from surveyed locations were grafted on healthy ridge gourd plants and maintained under greenhouse conditions for further studies. Mechanically inoculated ridge gourd plants (2-3 leaf stage) took four days to produce vein banding symptoms. Chlorotic lesions were observed on Chenopodium amaranticolor indicating the presence of Cucumber mosaic virus. When infected ridge gourd scions were wedge grafted on bitter gourd (Momordica charantia L.), pumpkin(Cucurbita moschata), ash gourd (Benincasa hispida), oriental pickling melon (Cucumis melo var. conomon) and ridge gourd (L. acutangula), expressed symptoms of infection 4-15 days after grafting (DAG). Grafted oriental pickling melon plants expressed low DI (33%). Seedlings raised from seeds collected from infected plants expressed pale banding symptoms (DI-15.38 %). Screening for disease resistance was undertaken with ten varieties/hybrids by wedge grafting with infected scion. After 20 days of grafting,the hybrid MHRG 7 recorded a high VI (65.33) and Arka Vikram recorded a low VI (39.33).After 40 days of grafting, hybrid Sorot F1 recorded high VI(78) and Arka Sujat recorded low VI(48). After 60 days of grafting, KRH-1 recorded the highest VI (91.33) while Arka Vikram recorded the lowest VI (66.67). RG7 and RG10 recorded moderately susceptible reactions to the virus. PCR based molecular detection of Tomato leaf curl New Delhi virus (ToLCNDV) using coat protein (CP) specific primers yielded amplicons of approximately 575 bp. The amplified PCR products were subjected to sequencing and blast analysis. All the isolated sequences were found to be related to ToLCNDV. Phylogenetic studies revealed that isolates from Thrikaripur, Mavichery, and Poolacode isolates were closely related to each other. DNA isolated from infected weeds like Synedrellasp., Alternanthera sp., graft transmitted different cucurbits such as bitter gourd, ash gourd, pumpkin, oriental pickling melon and ridge gourd detected the presence of begomovirus (575 bp amplicon). Cucumber mosaic virus was also detected from isolated samples using specific primers of CMV (CMV1 and CMV2) with an amplicon size of 400 bp. Thus, the study revealed that the ridge gourd cultivated in areas of Kasaragod, Kannur, and Kozhikode were infected with ToLCNDV and CMV; transmitted to other cucurbitaceous hosts andRG7 and RG10 were moderately susceptible among the varieties and hybrids screened. The presence of the begomovirus was detected in weeds indicating its role in perpetuation and spread of the virus disease in the field. Future emphasis should be the standardization of an early detection method for the multiple viruses involved and the developmentof an integrated management strategy for virus disease associated with ridge gour
MSC IN Agriculture